Investigating the role of FADS family members in breast cancer based on bioinformatic analysis and experimental validation - Zhao, Tingting; Gao, Pingping; Li, Yanling; Tian, Hao; Ma, Dandan; Sun, Na; Chen, Ceshi; Zhang, Yi; Qi, Xiaowei (Frontiers in Immunology, 2023)
Breast cancer (BC) is the most common malignant tumor in women worldwide. Emerging evidence indicates the significance of fatty acid metabolism in BC. Fatty acid desaturase (FADS) is closely associated with cancer occurrence and development. Here, we through bioinformatic analysis and experimental validation to investigate the potential function of FADS in BC. Several public databases were used to determine mRNA/protein expression levels, prognostic significance, functional enrichment, genetic alterations, association with tumor-infiltrating immune cells, and related transcription factors and kinases. Breast cancer tissues showed higher and lower mRNA expression of FADS2/6/8 and FADS3/4/5, respectively; FADS1/2 upregulation was significantly correlated with clinical stages. FADS family members showing differential expression levels were associated with various clinical subtypes, clinical stages, lymph node metastasis status, copy number variants, DNA methylation, and miRNA regulation. FADS1/2/6 and FADS3/4/5 showed higher and lower protein expression levels, respectively, in BC tissues. Moreover, FADS1/7 up- and FADS3/8 downregulation predicted poor overall and recurrence-free survival, while FADS2/5 up- and FADS4 downregulation were associated with only poor recurrence-free survival. Receiver operating characteristic curves revealed that FADS2/3/4/8 were good diagnostic markers. Besides, FADS family members showed varying degrees of genetic alterations, and gene ontology and KEGG pathway enrichment analyses suggested their involvement in lipid metabolism; their expression level was correlated with immune cell infiltration levels. FADS2 was chosen for further validation analyses. We found FADS2 to be significantly overexpressed in breast cancer clinical tissue samples as well as in different breast cancer cells. The proliferation, migration, and invasion abilities of MDA-MB-231 and BT474 cells were significantly reduced after FADS2 knockdown. Altogether, our findings suggest that FADS1/2/3/4 can serve as potential therapeutic targets, prognostic indicators, and diagnostic markers in patients with breast cancer.